Capital flight: Meanings and measures - Beja, Edsel L, Jr (Archīum Ateneo, 2005)
Capital flight – the unrecorded export of capital from developing countries – often represents a significant cost for developing countries. It also poses a puzzle for standard economic theory, which would predict that poorer countries be importers of capital due to its scarcity. This situation is often reversed, however, with capital fleeing poorer countries for wealthier, capital-abundant locales. Using a common methodology for a set of case studies on the size, causes and consequences of capital flight in developing countries, the contributors address the extent of capital flight, its effects, and what can be done to reverse it.